Science teachers’ experiences of inquiry-based learning through a serious game: a phenomenographic perspective - Lameras, Petros; Arnab, Sylvester; de Freitas, Sara; Petridis, Panagiotis; Dunwell, Ian (Smart learning environments, 2021)
This study employed a phenomenographic approach to investigate science teachers’ conceptions of inquiry-based learning through a serious game. Simaula is a prototype game designed and used as a virtual practicum for eliciting understandings on how in-game inquiry was appeared to, or experienced by, the participating teachers. Group interviews with 20 secondary education science teachers revealed four qualitatively different ways of experiencing inquiry-based learning through Simaula: (a) as uncovering insights about student’s learning needs, interests and emotions; (b) as generating ideas and concepts for meaningful inquiry; (c) as a set of operations for designing and carrying out scientific research; and (d) as authentic inquiry for enabling knowledge building processes. Seven dimensions of variation have been identified viewed as contextual influences on conceptions of in-game inquiry constituting discernment of: epistemic inquiry-based learning modes; role of teacher; role of student; game-play focus; core mechanics focus; feedback and progress mechanics and game uncertainty. The results illuminated a partial in-game inquiry approach with distinct epistemic modes from developing empathy and meaning making to knowledge construction and knowledge building. The findings also indicated that game design elements played central role in shaping conceptions of in-game inquiry from focusing on rules and logic as means to completing the game’s level to understanding the complexity of core mechanics for developing and transferring in-game inquiry to the real classroom. This insinuates that distinct game design properties may be considered in terms of extending intrinsic in-game inquiry experiences to actual in-class inquiry practice.